Disseminating design methods: A proposal for how to publish design methods for industry users - Kindberg, Elin (My University, 2019)
ABSTRACT The division of Design & Human Factors at Chalmers University of Technology consists of researchers who have the vision to contribute to making products, services and workplaces designed to enable people to live and work in a meaningful and sustainable way. Over time, the researchers have developed several design methods which are not used in practice to the extent that they want. The methods do not reach users working with design, such as design students and design professionals, as they are intended to. Today, there are no standards regarding how to package these methods to make them available for the industry. Previous research within this field has found that there is a need to create a new design space, where the academical world and practice can meet and communicate. This project has been performed on behalf of the division of Design & Human Factors (DHF). The aim of this project was to investigate which design methods that were relevant to make accessible for the industry, and how they should be packaged to encourage users to create sustainable and meaningful design. The two research questions that the project answered was: ▪ Which design methods developed by the division of Design & Human Factors should be made available for the industry? ▪ How should these design methods be presented and packaged in order to be easy to use and access?. By performing in-depth interviews with researchers and user studies with design students and professional designers, the project provided a suggestion for what design methods should be available, and how to publish them. The project resulted in a suggestion that DHF design methods that are based on a process model form are suitable to make available for the industry. Process model methods have a concrete work process, is supportive and has a temporal sequence which is desirable for industry users. To help researchers publish their material, a publishing guide was generated in the project. The guide shows all parts that are suggested to be included when publishing design methods such as: clear name, interesting headline, short introduction, prerequisites for using the method, stepwise instruction, a short description of how to visualise the result and decisions, contact information and references.. By using this publishing guide as a base, a suggested concept for publishing design methods called Design and Human Factors Method Graphic Platform was created. The platform provides users with design methods which are easy visualised in an infographic. The platform aims to be a design space were users can collaborate, share information and inspire each other. The community will hopefully encourage a changed mindset and an increased willingness to create meaningful and sustainable design. This online platform is a suggestion and a first step when it comes to compiling and publishing DHF design methods into one channel. The online platform and the publishing guide need to be further tested by users.. These project conclusions intend to help the division of DHF in their future work of making their research more available for the users. In the long term, the division has the potential to become a division which is in the forefront when it comes to bridging academia and practice together in order to create good designs.
Keywords: Annan teknik; Innovation och entreprenörskap (nyttiggörande); Produktion; Other Engineering and Technologies; Innovation & Entrepreneurship; Production